The Concept of University Social Responsibility from the Perspective of Upper Direction - Gaete Quezada, Ricardo A. (Cuadernos de Administración, 2015)
The concept of university social responsibility is analyzed based on the understanding they have on the socially responsible behavior of the directors of four universities in the city of Antofagasta in Chile. The research was carried out through a qualitative approach, considering the semi-structured interview as an information gathering technique and the procedures of Grounded theory to analyze the proposals and experiences of the university directors on the problem studied. The results obtained are associated to the concept of university social responsibility, on the one hand with a process of professional formation that allows students to have greater contact with the social reality surrounding them, and on the other hand, with greater pertinence of the university work with the requirements and needs of society. It is concluded that university directors play an important role in the implementation of policies and actions that enhance the socially responsible behavior of universities, above all in the management of change in the organizational culture as a key success factor for this process